2020
DOI: 10.1155/2020/2729354
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Deep Sedation on Mechanical Power in Moderate to Severe Acute Respiratory Distress Syndrome: A Prospective Self-Control Study

Abstract: Mechanical power (MP) is a parameter for assessing ventilator-induced lung injury (VILI) in patients with acute respiratory distress syndrome (ARDS). Deep sedation inhibits the respiratory center and reduces the excessive spontaneous breathing in ARDS patients, thereby reducing transpulmonary pressure (Ptp) and lung injury. However, the effect of sedation on MP in ARDS patients is not yet clear. Therefore, the purpose of this study was to investigate the effect of deep sedation on MP in ARDS patients. Patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 29 publications
2
11
0
3
Order By: Relevance
“…The MP between survivors and non-survivors was similar only on Day 18 of ICU admission in all patients statistically. Our study not only con rmed that baseline MP was associated with mortality [11][12][13][14], but also found that the association persisted for 11 days. In the Kaplan-Meier curves of the ARDS group, the two curves were similar within the rst 10 days and separated later evidently.…”
Section: Discussionsupporting
confidence: 73%
See 2 more Smart Citations
“…The MP between survivors and non-survivors was similar only on Day 18 of ICU admission in all patients statistically. Our study not only con rmed that baseline MP was associated with mortality [11][12][13][14], but also found that the association persisted for 11 days. In the Kaplan-Meier curves of the ARDS group, the two curves were similar within the rst 10 days and separated later evidently.…”
Section: Discussionsupporting
confidence: 73%
“…This implied that the bene t of lower MP required a period of time to develop in patients with more severe pneumonia. Furthermore, deep sedation signi cantly reduced MP in patients with moderate to severe ARDS, thereby reducing the occurrence of VILI [14]. All the above suggested that MP might be the cause of VILI, resulting in increased mortality rate.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Pulmonary edema became worse over time, the area of lung ventilation gradually decreased or was lost, and MP progressively increased. Higher LUS in the death group represents more severe alveolar collapse, pulmonary edema, and lung consolidation [ 23 ]. In the process of mechanical ventilation, in order to maintain the collapsed lungs in an open state, the ventilator requires more mechanical power [ 19 , 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…Serpa et al reported that the MP of ventilation in the first 48 h is associated with mortality in critically ill patients in two observational cohorts. In patients with ARDS, initial MP was also associated with mortality [11][12][13]. These four studies all used a simplified equation proposed by Gattinoni et al to calculate MP in patients with volume-controlled ventilation [8,14].…”
Section: Introductionmentioning
confidence: 99%